Medical Physics - Voto Bernales, Juan (1927)
The elasticity of the vessel walls is considerable, they can experience very important temporary deformation. Thus, the arterial tissue undergoes, for the same section and the same tensioning weight, an elongation 17 times greater than the venous tissue or muscle and 1000 times greater than the tendons.